2018
DOI: 10.24869/psyd.2018.157
|View full text |Cite
|
Sign up to set email alerts
|

THE COMBINED EFFECT OF CYP2D6 AND DRD2 Taq1A POLYMORPHISMS ON THE ANTIPSYCHOTICS DAILY DOSES AND HOSPITAL STAY DURATION IN SCHIZOPHRENIA INPATIENTS (OBSERVATIONAL NATURALISTIC STUDY)

Abstract: In a cohort of schizophrenia inpatients CYP2D6 metabolic activity affects mean AP daily dose only in the presence of DRD2 Taq1A polymorphic allele. CYP2D6 metabolic activity correlates independently from DRD2 Taq1A polymorphism with hospital stay duration. Subpopulation of schizophrenia inpatients with altered CYP2D6 activity (PMs and UMs) carriers of Taq1A polymorphisms needs special attention of clinicians in aligning of AP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Interestingly, CYP2D6 metabolic activity affects mean antipsychotics daily dose only in the presence of DRD2 Taq1A polymorphic allele. Subpopulation of schizophrenia inpatients with altered CYP2D6 activity (poor and ultra rapid metabolizers) and when carriers of Taq1A polymorphisms needs special attention of clinicians in aligning of antipsychotic treatment (Kurylev et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CYP2D6 metabolic activity affects mean antipsychotics daily dose only in the presence of DRD2 Taq1A polymorphic allele. Subpopulation of schizophrenia inpatients with altered CYP2D6 activity (poor and ultra rapid metabolizers) and when carriers of Taq1A polymorphisms needs special attention of clinicians in aligning of antipsychotic treatment (Kurylev et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These processes include transport across biological membranes, such as absorption and excretion, and metabolism. Individuals with greater metabolism may require higher doses, while those with lower metabolic rates might be more prone to the drugs' adverse effects and need dose reduction [3][4][5][6][7] . With all these variables potential predictors of drug response, which of them, or combination of, is the best predictor of clinical endpoints, if at all.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed in patients with psychiatric conditions taking drugs not recommended based on genetic information showed that they have 69% more total health care visits, 67% more medical visits and three times more medical absence days compared to patients taking drugs recommended based on their genotypes [ 122 ]. Another study associated CYP2D6 PMs and UMs to longer hospital stay duration compared to EMs [ 123 ]. In 2013, Herbild et al [ 124 ] demonstrated cost-effectiveness of preemptive CYP2D6 or CYP2C19 genotyping in patients with schizophrenia.…”
Section: Pharmacokinetics/pharmacogenetics Implementationmentioning
confidence: 99%